The Last Word Political posters: communicators or decorations? - Lynette Fourie (Communicare)
Political posters are often described as the decorations of elections. However, on how effective or successful political posters really are in harvesting votes, the last word has not been spoken. Although no party has probably ever won or lost an election because of its posters, the power of posters should not be underestimated. Posters are generally more effective in raising awareness than actually persuading voters to vote for a specific party. Political posters contribute mainly to image building, the reinforcement of party support, and the visibility of the party, which could ultimately lead to a bandwagon effect (Trent & Friedenberg, 1995:269-271; Maarek, 1995:105). Judging by the effort that parties put into their poster campaigns, they certainly seem to regard them as more than mere decorative statements. The countless reports of vandalism of posters by the different parties (see Van Staaden, 2006; Van Wyk, 2006; Louw, 2006:9; Smith, 2006; De Beer, 2006:9) are testament to how important parties perceive posters. The Democratic Alliance (DA) felt so strongly about their posters that they (as they did in 2004) installed electronic sensors in certain areas on their posters to alert them of vandalism (Anon, 2006). Surely parties would not be lodging complaints and quarrelling over posters if they were not seen as vital to the electioneering process. Parties thus spend a large portion of their budgets on posters. They estimate the cost of a poster at about R10,00 per poster, excluding the logistical costs of putting posters up and taking them down. It is against this background that I will comment on the poster campaigns of the major political parties. My comments are mainly limited to posters that were available in Potchefstroom and the surrounding areas, as these are the posters that I personally observed. Still, reference will be made to some of the political hotspots, for example Cape Town, where the political campaigns enjoyed a high media profile. The comments will be directed at the themes addressed on the posters, the role of the party leaders on the posters, and the general appearance of these posters.